Higher T-Cell Responses Induced by DNA/rAd5 HIV-1 Preventive Vaccine Are Associated With Lower HIV-1 Infection Risk in an Efficacy Trial. (12th February 2017) - Janes, Holly E.; Cohen, Kristen W.; Frahm, Nicole; De Rosa, Stephen C.; Sanchez, Brittany; Hural, John; Magaret, Craig A.; Karuna, Shelly; Bentley, Carter; Gottardo, Raphael; Finak, Greg; Grove, Douglas; et al.
Summary: This paper summarizes an immune correlates analysis finding that CD8+ T cell immune responses to HIV-1 Env peptides matching the DNA/rAd5 vaccine studied in the HVTN 505 efficacy trial are strong inverse correlates of HIV infection in the vaccine group. Abstract: Background: It is important to identify vaccine-induced immune responses that predict the preventative efficacy of a human immunodeficiency virus (HIV)–1 vaccine. We assessed T-cell response markers as correlates of risk in the HIV Vaccine Trials Network (HVTN) 505 HIV-1 vaccine efficacy trial. Methods: 2504 participants were randomized to DNA/rAd5 vaccine or placebo, administered at weeks 0, 4, 8, and 24. Peripheral blood mononuclear cells were obtained at week 26 from all 25 primary endpoint vaccine cases and 125 matched vaccine controls, and stimulated with vaccine-insert-matched peptides. Primary variables were total HIV-1-specific CD4 + T-cell magnitude and Env-specific CD4 + polyfunctionality. Four secondary variables were also assessed. Immune responses were evaluated as predictors of HIV-1 infection among vaccinees using Cox proportional hazards models. Machine learning analyses identified immune response combinations best predicting HIV-1 infection. Results: We observed an unexpectedly strong inverse correlation between Env-specific CD8 + immune response magnitude and HIV-1 infection risk (hazard ratio [HR] = 0.18 per SD increment; P = .04) and between Env-specific CD8 + polyfunctionality and infection risk (HR = 0.34 per SD increment; P < .01). Conclusions: Further research is needed to determine if these immune responses are predictors of vaccine efficacy or markers of natural resistance to HIV-1 infection.